Experiential Avoidance and Self-Compassion in Chronic Pain - Costa, Joana (2013)
The present study investigates the role of coping, experiential avoidance and self-compassion on psychological distress prediction (i.e. depression, anxiety and stress symptoms). A battery of self-report questionnaires was used to assess coping, experiential avoidance, self-compassion and psychological distress in 103 adults with chronic pain from Portuguese primary health care units. Hierarchical Regression Analyses were performed and showed that experiential avoidance and self-compassion are the factors that mostly explain psychological distress. Our results suggest that when people with chronic pain are willing to remain in contact with particular private experiences without attempting to control them, reported less depression, anxiety and stress. Implications for clinical practice were discussed, suggesting the importance of help people with chronic pain to increase their willingness to pain rather than avoid it.